Biomechanical Modeling to Improve Coronary Artery Bifurcation Stenting: Expert Review Document on Techniques and Clinical Implementation - Antoniadis, Antonios P; Mortier, Peter; Kassab, Ghassan; Dubini, Gabriele; Foin, Nicolas; Murasato, Yoshinobu; Giannopoulos, Andreas A; Tu, Shengxian; Iwasaki, Kiyotaka; Hikichi, Yutaka; Migliavacca, Francesco; Chiastra, Claudio; et al. (JACC. Cardiovascular interventions, 2015)
Treatment of coronary bifurcation lesions remains an ongoing challenge for interventional cardiologists. Stenting of coronary bifurcations carries higher risk for in-stent restenosis, stent thrombosis, and recurrent clinical events. This review summarizes the current evidence regarding application and use of biomechanical modeling in the study of stent properties, local flow dynamics, and outcomes after percutaneous coronary interventions in bifurcation lesions. Biomechanical modeling of bifurcation stenting involves computational simulations and in vitro bench testing using subject-specific arterial geometries obtained from in vivo imaging. Biomechanical modeling has the potential to optimize stenting strategies and stent design, thereby reducing adverse outcomes. Large-scale clinical studies are needed to establish the translation of pre-clinical findings to the clinical arena.